Doxifluridine promotes host longevity through bacterial metabolism. - Rui Wei; Yuling Peng; Yamei Luo; Xinyuan Wang; Zhenzhong Pan; Ran Zhou; Huan Yang; Zongyao Huang; Yaojia Liu; Lunzhi Dai; Yuan Wang; Yan Zhang (PLoS Genetics)
Aging is associated with alternative splicing (AS) defects that have broad implications on aging-associated disorders. However, which drug(s) can rescue age-related AS defects and extend lifespan has not been systematically explored. We performed large-scale compound screening in C. elegans using a dual-fluorescent splicing reporter system. Among the top hits, doxifluridine, a fluoropyrimidine derivative, rescues age-associated AS defects and extends lifespan. Combining bacterial DNA sequencing, proteomics, metabolomics and the three-way screen system, we further revealed that bacterial ribonucleotide metabolism plays an essential role in doxifluridine conversion and efficacy. Furthermore, doxifluridine increases production of bacterial metabolites, such as linoleic acid and agmatine, to prolong host lifespan. Together, our results identify doxifluridine as a potent lead compound for rescuing aging-associated AS defects and extending lifespan, and elucidate drug's functions through complex interplay among drug, bacteria and host.